Etichal Aspects of Implementing Experimental Research Design in Science Education - Frantius, Deklin; Nahadi, Nahadi; Firman, Harry (INTELEKTIUM, 2024)
Science education aims to convey science to students so that science can be transmitted according to its nature. Various scientific studies have been conducted to develop better teaching strategies. The research was conducted with the principle of the scientific method, experimental research design. In principle, it aims to test a treatment of research objects. In educational research, the tested treatment or learning model will be applied to the experimental group while the control group will not receive the additional treatment. Methodologically, the design is certainly in accordance with the purpose of the hypothesis. However, this will certainly be contradictive to ethical issues if the involved research objects are humans. The principle of fairness needs to be considered between the experimental group and the control group. It is guaranteed that all participants receive the same benefits. Therefore, it is necessary to study the ethical aspects of experimental research design in science education.